Tapered reduced deep beam connection for long span steel moment frames. (1st October 2021) - Alemayehu, Robel Wondimu; Jung, Sihwa; Bae, Jaehoon; Lee, Chang-Hwan; Ju, Young K.
Highlights: The proposed deep beam-column connection is apt in low-to-moderate seismic zones. Total rotation demand is shared between the panel zone and two plastic hinges. Numerical and experimental tests were performed with a 1200 mm deep beam. Stable hysteresis response with better strength, stiffness, and energy dissipation. Abstract: Beam to column connection ductility and beam flexural stiffness are crucial parameters for seismic performance and drift control in moment-resisting frames. However, an increase in beam span and depth to obtain column-free flexible internal space affects these parameters negatively. In this paper, a new long-span deep beam-column connection detail is proposed with improved stiffness and adequate ductility for moment frames in low-to-moderate seismic zones. As panel zones can undergo plastic deformation beyond the joint rotation demand in low-to-moderate seismic zones, the beam flange and panel zone in the proposed connection are proportioned such that a stable yielding occurs in the panel zone and two plastic zones on the beam segment away from the beam-column interface. The beam flanges at the beam-column interface are thickened, widened, and tapered to control beam plastic hinge locations and mitigate distress resulting from significant panel zone plastic deformation. The performance of the proposed connection was evaluated through a full-scale cyclic load test and parametric finite element analysis on a beam-column connection with a 1200 mm deep beam. The test and finite element results showed the formation of plastic hinges at the anticipated locations. Furthermore, the connection exhibited stable hysteresis beyond the minimum rotation limits specified for intermediate moment frames (American code) and ductility class medium (Eurocode). Moreover, the connection effectively allowed balancing between beam and panel zone yielding while hindering beam flange distress associated with significant panel zone plastic deformation. Furthermore, a comparison between the proposed and welded unreinforced flange-welded web connection demonstrated improved ductility, stiffness, moment capacity, and energy dissipation capacity. Additionally, equations were proposed to quantify the improvements, and balance beam and panel zone energy dissipation.